Predictability of cross-country skiers' competitive performance in terms of sociological variables - Černohorski, Branimir (Kinesiologia Slovenica, 2006)
The purpose of the study is to establish the values of variables from the sociological area in predicting potential competitive performance in cross-country skiing. The sociological area, encompassing 11 variables, was studied within the MMPS model of potential performance (motor abilities, morphologicy, psychology, sociology). The sample consists of 48 cross-country from three competitive categories. The expert modelling procedure was used to obtain scores (1-10) for the potential performance of the subjects at all levels of the sociological area. An analysis of the correlation between these scores and the actual competitive performance criterion shows that the sociological area in all three categories of subjets is insignificantly correlated with their competitive performance. Nevertheless, due to the small number of subjects the results cannot be generalised. After two subjects from each category were eliminated, this correlation increased substantially; in the category of older junior men it even reached the level of statistical significance. The results show that the original expert modelling procedure in the sociological area deserves further research attention and should be verified on larger samples of subjects practising not only this sport but also other sports.
Keywords: ekspertno modeliranje; smučarski tek; sociologija športa; tekmovalna uspešnost; uspešnost